The Impact of University Brand Equity on Student Satisfaction and Engagement: A Study of Vietnamese Universities - Le Na, Tran Thi; Thi Men, Tran; Thuong, Ngo Tri; Duy, Le Dinh Khanh; Duc, Phan Xuan; Ngan, Nguyen Thi (International Review of Management and Marketing, 2025)
In the context of globalization and deeper international integration, higher education is facing significant challenges related to competition and sustainable development. Building and effectively managing university brands have become critical factors determining the success of universities. This study aims to examine the impact of university brand equity on the satisfaction and engagement of Vietnamese students. Specifically, the research focuses on analyzing how university brand equity influences student satisfaction and engagement, employing a structural equation modeling (SEM) approach to investigate the relationships among variables, including gender and academic year as moderating factors. Primary data were collected through online and offline surveys of Vietnamese students, resulting in 402 valid responses. Data processing and analysis were conducted using SPSS software, with hypothesis testing performed through T-tests and one-way ANOVA. The findings reveal that university brand equity is measured by four components: brand awareness, brand association, perceived quality, and brand loyalty. Furthermore, the results confirm that university brand equity significantly impacts the satisfaction and engagement of Vietnamese students.